Intrinsic Valley Polarization in Computationally Discovered Two‐Dimensional Ferrovalley Materials: LaI2 and PrI2 Monolayers (Adv. Theory Simul. 4/2022). Issue 4 (11th April 2022) - Sharan, Abhishek; Singh, Nirpendra
Abstract : Intrinsic Valley Polarization in Computationally Discovered Two‐Dimensional Ferrovalley Materials Due to broken inversion and time‐reversal symmetry, two‐dimensional magnetic materials with intrinsic valley polarization are exciting for valleytronics. In addition to charge and spin, electrons in these materials possess a valley degree of freedom, paving the way for faster, more efficient, miniaturized next‐generation electronics. In article 2100476, Sharan and Singh explore two new ferrovalley materials, LaI2 and PrI2 monolayers.